TRADISI BASIACUONG DESA KOTO TIBUN KECAMATAN KAMPAR KABUPATEN KAMPAR - Nover Yarna; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study examines the Tradition of Basiacuong Koto Tibun Kecamatan Kampar Kabupaten Kampar. Basiacuong is one of the language culture of Kampar custom in general, is also a custom of the people of Desa Koto Tibun. This custom is inherited from their ancestors. Basiacuong used by ninik mamak Kampar in various custom events or not, such as opening Undiong "Runding" at weddings, eating bejambau, inauguration of adat, festivity, naming of children, circumcision and others. In this research, examined the form of social capital contained in the tradition of basiacuong and also the system maintains the tradition of basiacuong. Researchers use the theory of the habitus, arena and capital of Bourdieu. The research method is qualitative descriptive with the number of research subjects 9 people consisting of ninik mamak persukuan, kemenakan persukuan, people who learn basiacuong, community leaders and society. The results of this study indicate that the form of social capital contained in the tradition basiacuong the social capital, cultural capital, and symbolic capital. The author finds the system to maintain the existence of basiacuong tradition. Social capital is an important aspect of the strategy being implemented. By establishing a very harmonious relationship, well and get familiar with it all with the ninik mamak persukuan, kemenakan persukuan and people learn basiacuong to maintain basiacuong. Then the system to maintain the existence of basiacuong tradition by teaching and coaching to the young generation to continue the tradition of basiacuong, kemenakan and ninik mamak from each tribe teach and nurture to the youth generation.Keywords: Tradition, Basiacuong, Social Capital